Mechanistic insights into clary sage oils role in wound healing: targeting oxidative stress and inflammatory pathways - Rehab Ahmed; Krishnaraju Venkatesan; Durgaramani Sivadasan; Nizar Sirag; Hassabelrasoul Elfadil; Gayathri Anbumani; Debadrita Saha (Frontiers in Pharmacology)
IntroductionClary sage essential oil (CSEO), extracted from Salvia sclarea, is known for its antioxidant and anti-inflammatory properties. While its general therapeutic benefits are recognized, its specific role in wound healing remains inadequately explored. This study investigates the effects of CSEO on oxidative stress, inflammatory cytokines, and tissue regeneration in a rat excision wound model.MethodsRats were subjected to full-thickness excision wounds and divided into treatment, reference and control groups. The treatment group received topical application of CSEO, while reference and controls received standard drug and soft paraffin respectively. Wound healing was evaluated by measuring wound contraction and epithelialization. Biochemical assays assessed oxidative stress and inflammatory markers, while immunohistochemistry was used to analyse CD68 expression. Histological examinations evaluated granulation tissue, collagen deposition, angiogenesis, and inflammatory infiltration.ResultsCSEO significantly enhanced wound contraction and epithelialization compared to controls. Biochemical analysis showed a reduction in oxidative stress markers. Immunohistochemical evaluation revealed decreased CD68 expression, along with significantly lower levels of pro-inflammatory cytokines TNF-α and IL-6. Histopathological findings demonstrated improved granulation tissue formation, increased collagen synthesis, enhanced angiogenesis, and reduced inflammatory cell presence in CSEO-treated wounds.DiscussionCSEO facilitates wound healing through its antioxidant and anti-inflammatory actions. The reduction in oxidative stress and inflammatory mediators, along with improved histological parameters, suggests that CSEO supports effective tissue repair. These findings highlight the therapeutic potential of CSEO as a natural wound-healing agent and support its further investigation in regenerative medicine.